Tubercular uterocutaneous fistula after caesarean section: A case report - Aditi Jindal; Himanshu Chaudhary; Monika Thakur (Elsevier, 2018)
A 29-year-old patient had undergone an elective lower-segment caesarean section (LSCS) five months previously at a district hospital. The operation and the immediate postoperative period were uneventful. After five months she presented back with a fistulous opening. A fistulogram revealed a connection between the uterus and the skin. Fistulous tract excision was planned. Intraoperatively there was communication between the skin and the uterine cavity, with extensive necrosis of the uterine wall. The patient gave her informed consent for excision of the fistulous tract and/or total abdominal hysterectomy. During surgery, it was deemed that there was no scope for excision, so the decision was made for a total abdominal hysterectomy. Histopathological examination confirmed tuberculosis and the patient responded well to anti-tubercular drugs. This case report describes a rare presentation of tubercular uterocutaneous fistula after caesarean section. Keywords: Uterocutaneous fistula, Tuberculosis, Lower-segment caesarean section